The Importance of Physical Education and Sports in the Organization of Modern Pedagogical Conditions and Needs (Eurasian Journal of Learning and Academic Teaching, 2022)
This article analyzes the prospects for future qualitative organization of physical education classes and its pedagogical necessity by enhancing the professional culture of future physical education teachers. The article is also based on the modern pedagogical methods, tools, available opportunities and the need for further improvement of the organization of physical education classes.